CURRENT APPROACHES TO THE RESEARCH OF ANAPHORICAL PROCESSES IN THE FRENCH-LANGUAGE DISCOURSE - Gurmak, Yuliya (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the analysis of modern approaches to the study of anaphoric processes based on the material of French-language discourse. Explications of the concept of anaphora by Ukrainian and foreign linguists are interpreted. The newest methodological principles of comprehensive analysis of anaphoric units in French discourse, namely the combination of linguistic and literary methods, have been further developed. It was revealed that the study of anaphoric elements is not limited to the classical problem of repetition, it must be considered in a communicative aspect. In the framework of the cognitive-communicative process, the method of discourse analysis is described. It is proved that in the process of studying the anaphoric nomination of linguistic analysis is not enough, it is necessary to appeal to the discursive context and discursive memory. The cognitive operations that the speaker performs on anaphoric nomens in his own discourse are defined. The pragmatic and functional aspects of the anaphora phenomenon, which are the subject of the study of interactionist linguistics, are considered. The paper states that in the cognitive-pragmatic aspect the anaphoric nomination performs important functions within the framework of the connectivity of the discourse. This phenomenon is broad, which can be presented not only explicitly but also implicitly, that is, the reader himself has to guess what is said in the text, based on his own experience, knowledge and associations. Anaphora can correspond both to the communicative and cognitive requirements, because it not only captures the fragments of the knowledge and experience of the speaker, but also gives him a certain form in accordance with the communicative plan and the pragmatic intentions of the speaker. The article contributes to further systematization of anaphoric means of language, characterized by expressive and informative potential. Consideration of the features of functioning of anaphoric nomens as the structure components of the French-language discourse can contribute to the further study of the semantic-stylistic organization of discourse in general. __________________ References • Gurmak, Yu. М. «Vyrazhennja ta funkcionuvannja vtorynnoi nominacii na riznyh rivnjah movy u polikulturnomu prostori.» Naukovi zapysky Nacionalnogo universytetu «Ostrozka akademija» 2 (70), Serija «Filologija» (2018): 68–72. • Kost, G. М., Gurmak, Yu. М. «Anafora jak odyn iz vydiv vtorynnoi nominacii u francuzkomu hudozhnomu teksti.» Naukovyj visnyk Volynskogo nacionalnogo universytetu imeni Lesi Ukrainky 1 (226), Serija: «Filologichni nauky» (2012): 70–74. • Demjankov, V. Z. «Pragmaticheskie osnovy interpretacii vyskazyvanija.» Izvestija AN SSSR, Ser. literatury i jazyka, tom 40, № 4 (Moskva, 1981): 368–377. • Popova, N. M. «Interpretacijne pole konceptu yak providnyk mizh jogo universalnistyu j lingvokulturnoyu markovanistyu.» Problemy semantyky, pragmatyky ta kognityvnoyi lingvistyky 35 (Kyiv, Logos, 2019): 83–96. • Shevchenko, I. S. «Kognityvno-pragmatychni doslidzhennja.» Dyskurs jak kognityvno-komunikatyvnyj fenomen (Harkiv, Konstanta, 2005): 105–117. • Bacry, Р. Les figures de style : et autres procédés stylistiques (Paris, Belin, 1992). • Berrendonner, A. «La phrase et les articulations du discours.» Le français dans le monde (Paris, Hachette, 1993): 20-26. • Charolles, L’anaphore : problèmes de définition et de classification (Verbum, 1991). • Corblin, Les formes de reprise dans le discours (Rennes, PUR, Université de Rennes, 1995). • Ducrot, O., Todorov, T. Dictionnaire encyclopédique des sciences du langage (Paris, Seuil, 1979). • Fall, Vignaux, G., Boivin, M. «L’anaphore: quelques orientations actuelles dans le contexte europeen.» Linguistica atlantica 16 (APLA, 1994): 45–58, access https://journals.lib.unb.ca/index.php/la/article/view/22480/26137 • Gaiffe, B., Reboul, A., Romary, L. «Les SN définis : anaphore, anaphore associative et cohérence.» Relations anaphoriques et (in)cohérence (Rodopi, 1997): 69–97, access https://hal.archives-ouvertes.fr/hal-00416589/document • Imehrar, La construction linguistique de la relation interpersonnelle dans les Lettres de Mme de Sévigné. Linguistique. Thèse pour obtenir la grade de Docteur (Université Paul Valéry - Montpellier III, 2016), access https://tel.archives-ouvertes.fr/tel-01537904 • Reboul, «Resolution de l’anaphore pronominale: semantique et/ou pragmatique.» Cahiers de linguistique française 10 (1989): 77–100, access https://clf.unige.ch/files/7814/4111/1643/05-Reboul_nclf10.pdf • Reichler-Béguelin, M.-J. «Anaphore, cataphore et mémoire discursive.» Pratiques : linguistique, littérature, didactique. L’organisation des textes 57 (1988): 15–43, access persee.fr/doc/prati_0338-2389_1988_num_57_1_1470 • Vergès, P., Apothéloz, D., Miéville, D. «Cet obscur objet du discours: operations discursives et representations sociales.» Revue europeenne des sciences sociales, 25, № 77 (Librairie Droz, 1987): 209–224. • Wiederspiel «Sur l’anaphore : du modèle «standard» au modèle «mémoriel».» Travaux de linguistique et de philologie 27 (1989): 95–113.